2022
DOI: 10.1557/s43577-022-00301-w
|View full text |Cite
|
Sign up to set email alerts
|

Recycling rare earths: Perspectives and recent advances

Abstract: Rare-earth element (REE) demand is expected to increase by a factor of up to 7 by 2040. Recycling avoids the significant hurdles associated with opening new mines, but collection and disassembly of REE-containing devices are barriers. Absolute and relative abundances of REEs and co-occurring constituents differ significantly in secondary compared to primary sources, presenting challenges and opportunities. REE concentrations are typically low, but manufactured devices include only the desired REE, avoiding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Using system dynamics modelling incorporating life cycle assessment, Golroudbary 10 found that rapid development of green energy technologies could lead to an unsustainable consumption of REE. In light of these concerns, there has been substantial interest in extracting REE from alternative sources including recycling, 3,11,12 acid mine drainage systems, [13][14][15] mining waste, 16,17 geothermal and oileld brines, 18,19 and coal combustion by-products (CCBs). [20][21][22][23] Among these, coal combustion by-products are emerging as a promising source of REE based on several factors including: (i) availability as a low-cost waste product with strong incentives for reuse due to environmental liabilities of ash storage; (ii) a reduced requirement for excavation or beneciation thereby eliminating the most energy intensive processes involved in REE mining; and (iii) the elimination of radioactive tailings.…”
Section: Introductionmentioning
confidence: 99%
“…Using system dynamics modelling incorporating life cycle assessment, Golroudbary 10 found that rapid development of green energy technologies could lead to an unsustainable consumption of REE. In light of these concerns, there has been substantial interest in extracting REE from alternative sources including recycling, 3,11,12 acid mine drainage systems, [13][14][15] mining waste, 16,17 geothermal and oileld brines, 18,19 and coal combustion by-products (CCBs). [20][21][22][23] Among these, coal combustion by-products are emerging as a promising source of REE based on several factors including: (i) availability as a low-cost waste product with strong incentives for reuse due to environmental liabilities of ash storage; (ii) a reduced requirement for excavation or beneciation thereby eliminating the most energy intensive processes involved in REE mining; and (iii) the elimination of radioactive tailings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a variety of organizations that have emerged. These organizations have moved forward with strategies that are centred on separation, recycling, recovery and reusing the resources that we have at our disposal (Fujita et al 2022). Designing and developing sustainable processes for recycling and reusing energy-critical materials, such as rare earth metals, that come from the use of used products has become a long-term challenge.…”
Section: Al 2019)mentioning
confidence: 99%
“…1 a, b [ 13 – 15 ]). Reviews with more information on the specific processes and challenges of REE mining are available from Xie et al [ 16 ] and REE recycling from Ginosar et al [ 17 ].
Fig.
…”
Section: Benefit I: Coproduction Of Metalsmentioning
confidence: 99%